Survival analysis of adult patients with ALL in Mexico City: first report from the Acute Leukemia Workgroup (ALWG) (GTLA) - Erick Crespo‐Solis; Karla Espinosa‐Bautista; Martha Alvarado‐Ibarra; Etta Rozen‐Fuller; Fernando Pérez‐Rocha; Chantal Nava‐Gómez; Maricela Ortiz‐Zepeda; José Luis Álvarez‐Vera; Christian Omar Ramos‐Peñafiel; Luis Antonio Meillón‐García; Sergio Rodríguez‐Rodríguez; Alan Pomerantz‐Okon; et al. (Cancer Medicine, 2018)
Abstract Acute lymphoblastic leukemia (ALL) is a hematologic malignancy characterized by the clonal expansion of hematopoietic lymphoid progenitors. With new target therapies, the survival of adults with ALL has improved in the past few decades. Unfortunately, there are no large ALL patient series in many Latin American countries. Data from the Acute Leukemia Workgroup that includes five Mexico City referral centers were used. Survival was estimated for adult patients with ALL during 2009–2015. In total, 559 adults with ALL were included. The median age was 28 years; 67% were classified into the adolescent and young adult group. Cytogenetic information was available in 54.5% of cases. Of the 305 analyzed cases, most had a normal caryotype (70.5%) and Philadelphia‐positive was present in 16.7%. The most commonly used treatment regimen was hyper‐CVAD. In approximately 20% of cases, there was considerable delay in the administration of chemotherapy. Primarily refractory cases accounted for 13.1% of patients. At the time of analysis, 26.7% of cases had survived. The 3‐year overall survival was 22.1%. The main cause of death was disease progression in 228 (55.6%). Clinical and public health strategies are needed to improve diagnosis, treatment and survivorship care for adult with ALL. This multicentric report represents the largest series in Mexico of adult ALL patients in which a survival analysis and risk identification were obtained.